Impact of extreme debris flow-induced paleodamming events on the sedimentological evolution of the middle Yarlung Tsangpo River reaches since the late Pleistocene, Tibet - Wang, Huiying; Wang, Ping; Hu, Gang; Yuan, Renmao; Ge, Yukui; Xu, Bo; Shi, Lingfan (Frontiers in Earth Science, 2023)
As extreme surface processes, long-term river damming and outburst events can impact sediment supply and transportation in valleys and therefore significantly change the landscape. Lacustrine sediments were identified in the wide Xigaze Valley, in the middle reaches of the Yarlung Tsangpo River in Tibet, an area which has been considered to have been a paleodammed lake. However, the evolutionary process and damming mechanisms associated with this paleolake, and any subsequent impact on sedimentation within the valley, remain unclear. Here, we present a detailed geomorphological and sedimentary analysis of the proposed paleolake area, based on a study of a prominent valley fill found along a section of the Yarlung Tsangpo River and its tributary that flows into it from the south, the Menchu River. This section stretches from Xigaze to Dazhuka. Sedimentary facies analysis of two stratigraphic sections in Renbu Town showed that at least two paleolakes caused by debris flow related to glaciers developed in the Xigaze Valley and that the paleodam was located near the outlet of the Dazhuka Gorge. Chronological constraints suggest that the first damming event occurred between ∼48.6 and 33.7 ka in Marine Isotope Stage (MIS) 3 and had a minimum lake surface elevation of ∼3,820 m. The second damming occurred between ∼24.3 and 12.7 ka during the Last Glacial Maximum (LGM), producing a lake surface elevation of at least ∼3,760 m. During the development of the paleolakes in the Xigaze Valley, several small-scale damming and outburst events happened in the upper and middle reaches of the Menchu River, resulting in fluviolacustrine and outburst flood sediments accumulating in the main stream of the Yarlung Tsangpo River and forming thick-fill terraces. We presumed that the paleolakes in the middle reaches of the Yarlung Tsangpo River gradually drained as a result of continuous overflow undercutting instead of outburst flood events, thereby allowing fluvial aggradation of the upper reaches of the paleodam.